Development of Hetrik Mobile Application in Iot-Based Electricity Management for Boarding Houses - Moch. Azam Firmansyah; Ronald David Marcus (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
Inefficient electricity usage is a common issue in boarding houses due to limited transparency in consumption data and the absence of integrated real-time monitoring systems. To address this problem, this study proposes an Internet of Things (IoT)-based mobile application called Hetrik to support more transparent and efficient electricity management. The research aims to design and implement an integrated system architecture that connects IoT-based sensing hardware with a digital user interface for monitoring and managing electricity consumption. The system was developed using the Agile development method, consisting of requirement analysis, system design, development, testing, implementation, evaluation, and deployment stages. The hardware architecture integrates an ESP32 microcontroller with ACS712 current sensors and ZMPT101B voltage sensors to capture real-time electricity consumption data. The mobile application was developed using React Native for the front-end and Laravel for the back-end and cloud database. A key contribution of this research is the design and validation of a QR-to-Device scanning mechanism, which enables dynamic mapping between IoT device identities and user accounts while supporting an automatic prepaid electricity payment system. System implementation produced five core modules: power monitoring dashboard, transaction system, usage history, profile management, and device scanning. Functional testing using the Black Box method and User Acceptance Testing (UAT) confirmed that the system operates according to technical specifications and is suitable for real operational environments. The proposed system demonstrates the potential to reduce electricity waste in boarding houses by up to 30% through data-driven energy monitoring and management.